Analysis and optimization machining parameter base on different type of material in incremental forming process (ALGOR simulation) - Mohd Hisham, Sidi Ahmad (2009)
This research was carried out to develop and analysis of an incremental forming machine controlled by personal computer numerical control (PCNC) and ALGOR software for simulation. Incremental Sheet Forming (ISF) is one kind of sheet metal forming. It is based on using of simple spherical tool, which is moved along personal computer (PC) controlled tool path. Aim of this study is analysis in stepdown for new development of incremental forming. The paper presents the analyses about the implication and justification for forming process. Using FE analysis have been achieved with the purpose to compare between experimental and simulation. The process and analysis have been use to determine the stepdown in the design phase for continuous operation. Additionally, this paper also shows investigate the effect different type of material on yield stress and Springback and investigate the deformation mechanics under an optimization with different type of material.